Analisis Kegunaan Microsoft Lync serta Fitur dan Keunggulan dalam Efektivitas Berkomunikasi - Hajrah Rahmah; Arya Zidan Riza Pratama; Ilham Salim Siregar; Ekry Syahriwanda (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This1study1aims1to1analyze1and1identify the1use of Microsoft Lync in communication and its use in the professional1world1of1work.1This1study1used1qualitative1research1method.1This research is based on journal documents, articles and books. In this study, the sample was selected using an analytical technique which selects the data and then sorts the information well from the existing data sources, then summarizes it without reducing the original information from the document. The selected sample is data information about Microsoft, the Internet, servers, and Microsoft Office from the 2010 version to the latest version 2013, which contains an overview of the understanding and features in Microsoft Lync to its advantages. The results showed (1) the definition of Microsoft Lync and its server; (2) Microsoft Lync features that make work easier, and (3) Microsoft Lync's advantages in its use in the professional-grade world of work.